A experiência da saúde coletiva na formação profissional: retrato da extensão universitária - Moimaz, Suzely Adas Saliba [UNESP]; Santos, Renata Reis dos [UNESP]; Saliba, Orlando [UNESP]; Borges, Heloisa Carvalho [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Arcieri, Renato Moreira [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2013)
The guidelines of National Curriculum for Dental courses highlights the necessity in providing for the professional the ability to analyze and assess community’s problems and needs, and to create solutions for the society. The continuing education may be considered a useful tool for the teaching and learning because it favors the diversification of learning environments, which allows the insertion of undergraduate and graduate students into the real scenarios. This current study aimed to assess the Public Health projects and programs of the UNESP – Araçatuba Dental School, by describing the interaction experiences between faculty and health services in the professional career development. Historical, documentary and descriptive searches were performed based on the faculty archives such as official documents, reports, databases from the Pro-rector of continuing education and published papers in the period between 1964 and 2011. The following experiences were noted: the Extra-Muro Dental Service (SEMO), established in 1964, that focused in providing dental treatment to the rural population, highlighted the social inclusion of discriminated society groups since that time. In 1972, this service was expanded to several specific populations living in the urban areas. In the '60s, many educational campaigns were performed as homemade water filter and construction of wells and septic tanks which demonstrate the concern with the determinants of healthdisease process. At that time, the campaign of fluoridation of public water supplies in several counties started as Araçatuba, Birigui, Penápolis, Guararapes, Valparaíso and so on. The Campaign of “Good Teeth” from the '70s became wider over time and it was transformed in the "Oral Health Education Program" and it was continuously developed in all public schools of Araçatuba and some neighboring towns, benefiting children aged from 6 to 10 years-old. Several epidemiological studies of caries, periodontal diseases, malocclusion and fluorosis were conducted in cooperation with local governments, and counted with the participation of undergraduate and graduate students. Pereira Barreto – SP was the precursor city in Brazil to carry out fluorosis study. Currently, 12 projects of Public Health from the Institution of Higher Education in the Pro-rector of continuing education are being developed. The concern in qualifying the human resources in health is confirmed with the development of training courses and workshops for professionals, highlighting the training for people enrolled in the Family Health program; Community Health Agent training - Solidarity University, and Municipal Health Counselors training. The Graduate Program in Social and Preventive Dentistry, created in 1993, has an important role to train several professionals for the Unified Health System, and provides education to create researchers, professors and administrators, and enucleates research groups in several Brazilian states. In all activities showed herein, a dynamic participation of undergraduate and graduate students has been observed, and several books, guidelines, articles, brochures and booklets have been published as a result of the continuing education activities.. It was concluded that different projects and programs have been developed by the Public Health of UNESP –Araçatuba Dental School, which allow the exchange of experience between the university and health services, and benefit all participants enrolled in these activities.

Las Directrices Curriculares Nacionales para los Cursos de Odontología explican la necesidad de la formación de un profesional capaz de analizar los problemas de una comunidad, evaluar las necesidades, y obtener soluciones para los mismos. La actividad de extensión puede ser considerada una herramienta eficaz de enseñanza-aprendizaje, pues favorece la diversificación de los ambientes de aprendizaje, permitiendo la inserción de los alumnos de pre-grado y post-grado en escenarios reales. El objetivo en este trabajo fue verificar los proyectos y programas, en el área de salud colectiva, relatando las experiencias de integración academia-servicios de salud en la formación profesional desenvueltos por la UNESP-FOA. Fue realizada una investigación histórica, documental, descriptiva, con consulta de los archivos institucionales, considerando: textos oficiales, informes, documentos, banco de datos de la pro-rectoría de extensión y artículos publicados, en el periodo de 1964 a 2011. Se verificaron las siguientes experiencias: Servicio Extra-Muro Odontológico (SEMO), creado en 1964, objetivando la atención odontológica a la populación rural, evidenciando que en aquella época ya había entendimiento de la inclusión social de grupos olvidados. En 1972, el servicio fue ampliado para zona urbana, para varias populaciones específicas. En los anos 60 fueron realizadas varias campañas educativas: Filtro casero y construcción de pozos y fosas, demostrando la preocupación con los determinantes del proceso salud-enfermedad. En aquel momento se iniciaron también las campañas para fluorización del agua de abastecimiento público en diversos municipios: Araçatuba, Birigui, Penápolis, Guararapes y Valparaíso, entre otros. La Campaña de los “Buenos Dientes”, realizada en los años 70, con el pasar de los años, tomó grandes dimensiones, tornándose el “Programa de Educación en Salud Bucal”, desenvuelto de forma continua, en todas las escuelas públicas de Araçatuba y en algunas ciudades vecinas, beneficiando a los niños de 6 a 10 años de edad. Diversos estudios epidemiológicos de campo fueron realizados en asociación con las prefecturas municipales, todos con la participación de alumnos de pregrado y/o post-grado: caries, periodontopatías, oclusopatías y fluorosis dental, en diferentes municipios, destacándose el estudio pionero en Brasil, sobre esta última afección, realizado en Pereira Barreto-SP. Actualmente están registrados y en desenvolvimiento 12 proyectos en la Salud Colectiva de la IES en la Pro-rectoría de Extensión de la Universidad. La preocupación con la calificación de recursos humanos en salud está demostrada, con el desenvolvimiento de entrenamientos, cursos y conferencias para los profesionales de la red de la salud, destacándose las capacitaciones para los equipos de Salud de la Familia; Formación y Capacitación del Agente Comunitario de Salud – Universidad Solidaria; Formación y Capacitación de Consejeros Municipales de Salud. En la formación de profesionales para el SUS, se evidencia el papel del programa de Post-Grado en Odontología Preventiva y Social, creado en 1993, formando investigadores/profesores/gestores y enucleando grupos de investigación, en varios estados brasileños. En todas las actividades consta la participación activa de los alumnos de pre-grado y post-grado y como productos generados, resultantes de las actividades de extensión fueron encontrados diversos libros, manuales, artículos, folders y cartillas. Se concluyó que diferentes proyectos y programas han sido desenvueltos por la salud colectiva de la UNESP-FOA, permitiendo intercambio de experiencia entre la universidad y los servicios de salud, con beneficios a todos los involucrados.

As Diretrizes Curriculares Nacionais para os Cursos de Odontologia explicitam a necessidade de formação de um profissional capaz de analisar os problemas de uma comunidade, avaliar as necessidades e obter soluções para os mesmos. A atividade de extensão pode ser considerada uma ferramenta eficaz de ensino-aprendizagem, pois favorece a diversificação dos ambientes de aprendizagem, permitindo a inserção dos alunos de graduação e pós-graduação em cenários reais. O objetivo, neste trabalho, foi verificar projetos e programas, na área de saúde coletiva, relatando as experiências de integração academia-serviços de saúde na formação profissional desenvolvidos pela UNESP-FOA. Foi realizada uma pesquisa histórica, documental, descritiva, com consulta aos arquivos institucionais, considerando: textos oficiais, relatórios, documentos, banco de dados da pró-reitoria de extensão e artigos publicados, no período de 1964 a 2011. Verificaram-se as seguintes experiências: Serviço Extra-Muro Odontológico (SEMO), criado em 1964, objetivando a atenção odontológica à população rural, evidenciando que naquela época já havia o entendimento da inclusão social de grupos negligenciados. Em 1972, o serviço foi ampliado para zona urbana, para várias populações especificas. Nos anos 60, foram realizadas várias campanhas educativas: Filtro caseiro e Construção de poços e fossas, demonstrando a preocupação com os determinantes do processo saúde- doença. Naquele momento, iniciaram-se também as campanhas para fluoretação das águas de abastecimento público em diversos municípios: Araçatuba, Birigui, Penápolis, Guararapes e Valparaíso, dentre outros. A Campanha dos “Bons Dentes”, realizada nos anos 70, com o passar dos anos, tomou dimensões amplas, tornando-se o “Programa de Educação em Saúde Bucal”, desenvolvido de forma contínua, em todas as escolas públicas de Araçatuba e em algumas cidades vizinhas, beneficiando crianças de 6 a 10 anos de idade. Diversos estudos epidemiológicos de campo foram realizados em parceria com as prefeituras municipais, sendo que em todos houve participação de alunos de graduação e/ou pós-graduação. Os temas abordados foram: cárie, periodontopatias, oclusopatias e fluorose dentária, em diferentes municípios, destacando-se o estudo pioneiro no Brasil, sobre esta última afecção, realizado em Pereira Barreto (SP). Atualmente estão cadastrados e em desenvolvimento 12 projetos na Saúde Coletiva da IES na Pró-reitora de Extensão da Universidade. A preocupação com qualificação de recursos humanos em saúde fica demonstrada por meio do desenvolvimento de treinamentos, cursos e palestras para os profissionais da rede pública de saúde, destacando-se as capacitações para as equipes da Saúde da Família; Formação e Capacitação de Agente Comunitário de Saúde – Universidade Solidária; Formação e Capacitação de Conselheiros Municipais de Saúde. Na formação de profissionais para o SUS, evidencia-se o papel do programa de Pós-Graduação em Odontologia Preventiva e Social, criado em 1993, formando pesquisadores/professores/gestores e nucleando grupos de pesquisa, em vários estados brasileiros. Em todas as atividades, consta participação ativa dos alunos de graduação e pós-graduação e como produtos gerados, resultantes das atividades extensionistas foram encontrados diversos livros, manuais, artigos, folders e cartilhas. Conclui-se que diferentes projetos e programas têm sido desenvolvidos pela saúde coletiva da UNESP-FOA, permitindo troca de experiência entre universidade e serviços de saúde, com benefícios a todos os envolvidos.
The experience of career training in public health: portrait of continuing education
La experiencia de la salud colectiva en la formación profesional: retrato de la extensión universitaria
Keywords: Education; Dental; Community-institutional relations; Teaching; Educación en odontología; Relaciones comunidad-institución; Ensenãnza; Educação em odontologia; Relações comunidade-instituição; Ensino